The Georgian-Abkhaz Conflict / Chapter 5 of Europeanization and Conflict Resolution: Case Studies from the European Periphery - Bruno Coppieters (Journal on Ethnopolitics and Minority Issues in Europe, 2004)
This chapter analyses the historical background to the secessionist conflict in Abkhazia and the prospect of a settlement. The Georgian-Abkhaz conflict, driven by a need for identity and security, is one that failed to be resolved within the hierarchical federal framework of the Soviet state. Abkhazia seceded from Georgia as a result of the 1992-93 war. UN mediation has so far failed to bring a political settlement closer. The chapter describes the solutions proposed and political actions taken both by the parties to the conflict and by the external mediators. It assesses the way in which the conflicting parties perceive the process of Europeanization in their region, the role of the European Union in the conflict on Abkhazia, and possible future outcomes. The UN proposals for a settlement make it possible to envisage the future of Abkhazia either as part of a federation with Georgia or as an associated state with Georgia, but as long as the external powers are unable to devise a common approach to overcoming the present deadlock in the political negotiations, it remains difficult to predict the precise outcome of the conflict.